Urban river health assessment and management - Pinto, U.; Dickens, Chris; Babel, M.; Maheshwari, B. (Elsevier, 2024)
River systems in the world are under enormous pressure due to urbanization together with agricultural and industrial development and the effects of climate variability and change. Especially the urban segments of river systems are prone to additional pressures due to multiple points and nonpoint source discharges and impervious catchments that lead to rapid stormwater runoff of generally polluted water, all of which leads to degradation of river health. River health has been defined in many ways, often focusing on environmental aspects and ignoring social, cultural, and economic dimensions. This is mainly because natural river systems are distributed over a large geographical space with unique biotic and abiotic characteristics, where socio-economic and cultural perspectives of communities change vastly. In an urban context, however, for rivers to be sustainable, management strategies need to consider the broader meaning of river health to include socio-cultural aspects with the physio-chemical and biological nature of the river water. This chapter reviews a wide range of single and multimetric indicators and overarching frameworks used in different jurisdictions to assess the health of river systems and provide best practice recommendations for urban river health management. The chapter proposes systematic and integrated monitoring to understand the system’s health better. It promotes the understanding of urban river systems and recommends implementing a transdisciplinary approach for river management by harmonizing policy, involving active and passive users, with targeted monitoring and research efforts to reduce pressures and improve the condition of urban rivers.